Research progress of plant medicine and Chinese herbal compounds in the treatment of rheumatoid arthritis combined with osteoporosis - Gu, Zhuoxu; Zhou, Guanghui; Zhang, Xianquan; Liang, Guihong; Xiao, Xiao; Dou, Yaoxing (Frontiers in Medicine, 2024)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease, the clinical manifestations of various joint pain and bone destruction is common, high disability rate, and is closely related to local and systemic osteoporosis (OP). RA can occur at any age, its incidence increased with the increase of age on the rise, most of the patients were 40 ~ 50 years old crowd, female incidence of about 3 ~ 5 times as much as men, osteoporosis is a kind of characterized by bone mass and bone microstructure damage of metabolic bone disease, is one of the common complications of RA. Nowadays, in the clinic, more patients develop RA with OP symptoms. Therefore, both OP and RA-related factors should be considered in the OP treatment of RA. Nowadays, there are more and more researches on RA combined with OP drugs, including basic drugs, bone resorption inhibitors, bone formation promoters and anti-rheumatic drugs to improve the condition. The high cost or limited efficacy of certain western drugs, coupled with their potential for adverse reactions during treatment, highlight the pressing need for novel 删除了: traditional